Classification and analysis of quantitative and qualitative variables in fluoride monitoring data collected from animal feed products - Andrea Trossi; Paola Brizio; Maria Leogrande; Caterina Stella; Chiara Marchese; Giulia Mastellone; Maria Cesarina Abete; Stefania Squadrone (Scientific Reports)
Abstract Fluorides are substances that can occur in animal feed and considered undesirable for their subacute toxicity. Restrictions were therefore established by current European laws, with different maximum levels according to matrices, and monitoring of animal feed started in EU since 2018. In this study a dataset of 299 fluoride determinations carried out in Italy in the 2018–2023 was analyzed by mean of advanced descriptive statistics. The activities were done referring to two quantitative and two qualitative variables classified in decreasing order with respect to the information level and according to an international standard: fluoride content, year, region of provenance and matrix subtype. A set of multi-way tables - designed around fluoride values above the limit of quantification (LOQ) - highlighted that 90% of the samples are free of fluorides. A constant decrease in number of samples containing fluoride was detected over the years, without samples exceeding the regulation limits. Powdered phosphates, raw materials and mineral raw materials were the matrices with the highest content of fluoride.